Falls from height: analysis of 114 cases - Tomi Zlatar; Eliane Maria Gorga Lago; Willames de Albuquerque Soares; João dos Santos Baptista; Béda Barkokébas Junior (Production)
Abstract Paper aims To study fall-accident cases in order to analyze the commonly missing or not adequately applied risk management measures (RMM) and its consequences depending on falling height. Originality First study to analyze failed RMM for preventing falls from height. Research method The study reviewed court cases published by the journal “Safety & Health Practitioner”. NIOSH recommendations were used to define RMM to apply to this study. Main findings Finally, in 98% of analyzed cases, the fall from height was a result of several non-adequate or missing RMM: in 81.6% procedures of work, 65.8% guardrails and edge protection, 60.5% risk assessment, and 60.5% platforms or scaffolds. It can be concluded that falls from height pose a significant risk for workers, which could be prevented by adequately apply RMM. Implications for theory and practice The focus in the prevention of falls should be given on most common RMM.